Studi Kasus: Dinamika Psikologis pada Perempuan yang Mengalami Gangguan Konversi - Ni Made Putri Ariyanti; Tri Kurniati Ambarini; Putu Nugrahaeni Widiasavitri (Humanitas (Jurnal Psikologi), 2024)
Conversion Disorder is classified as a somatoform disorder characterized by symptoms or deficits that are not clearly defined and affect motor or sensory functions related to neurological conditions or other general medical conditions. Hearing impairment in conversion disorder is referred to as non-organic hearing loss. This research aims to understand the dynamics in women with conversion disorder and the causes of the disorder. The approach used in this study is qualitative with a case study approach. Data collection in this study uses interviews, observations, and psychological tests (DAP, HTP, BAUM, SSCT, TAT, and SPM). The credibility test used is the triangulation technique of sources, techniques, and time. The subject in this study is a 36-year-old woman. The results of this study indicate that the individual has hearing problems not caused by a medical condition. The hearing difficulties arise due to conflicts and impulses triggered by stressful conditions in marital life, leading the person to repress to avoid threats to the issue. As a result, unconsciously, the individual transforms it into physical symptoms. This affects both the individual's work and social aspects.